Direct Synthesis of 1, 6‐Hexanediol from HMF over a Heterogeneous Pd/ZrP Catalyst using Formic Acid as Hydrogen Source. Issue 1 (20th November 2013) - Tuteja, Jaya; Choudhary, Hemant; Nishimura, Shun; Ebitani, Kohki
Abstract A new approach is developed for hydrogenolytic ring opening of biobased 5‐hydroxymethylfurfural (HMF), dehydration product of hexoses, towards 1, 6‐hexanediol (HDO) under atmospheric pressure. The highest yield of HDO, 43 %, is achieved over reusable Pd/zirconium phosphate (ZrP) catalyst at 413 K in the presence of formic acid as hydrogen source. In comparison with various Brønsted and/or Lewis acidic supports, the specific Brønsted acidity on ZrP support effectively accelerated the cleavage of CO bond in a furan ring.